Seismic Performance Assessments of RC Frame Structures Strengthened by External Precast Wall Panel - Seung-Ho Choi; Jin-Ha Hwang; Sun-Jin Han; Hyo-Eun Joo; Hyun-Do Yun; Kang Su Kim (Applied Sciences, 2020)
In recent years, a variety of strengthening methods have been developed to improve the seismic performance of reinforced concrete (RC) frame structures with non-seismic details. In this regard, this study proposes a new type of seismic strengthening method that compresses prefabricated precast concrete (PC) walls from the outside of a building. In order to verify the proposed method, a RC frame structure strengthened with precast walls was fabricated, and cyclic loading tests were performed. The results showed that specimens strengthened using the proposed method exhibited further improvements in strength, stiffness and energy dissipation capacity, compared to RC frame structures with non-seismic details. In addition, a nonlinear analysis method, capable of considering the flexural compression and shear behaviors of the walls, was suggested to analytically evaluate the structural behavior of the frame structures strengthened by the proposed method. Using this, an analysis model for frame structures strengthened with precast walls was proposed. Through the proposed model, the analysis and test results were compared in relation to stiffness, strength, and energy dissipation capacity. Then, the failure mode of the column was evaluated based on the pushover analysis. In addition, this study proposed a simplified analysis model that considered the placement of longitudinal reinforcements in shear walls.